Gynura procumbens: An Overview of the Biological Activities - Tan, Hui-Li; Chan, Kok-Gan; Pusparajah, Priyia; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Pharmacology, 2016)
Gynura procumbens (Lour.) Merr. (Family Asteraceae) is a medicinal plant commonly found in tropical Asia countries such as China, Thailand, Indonesia, Malaysia and Vietnam. Traditionally, it is widely used in many different countries for the treatment of a wide variety of health ailments such as kidney discomfort, rheumatism, diabetes mellitus, constipation and hypertension. Based on the traditional uses of G. procumbens, it seems to possess high therapeutic potential for treatment of various diseases making it a target for pharmacological studies aiming to validate and provide scientific evidence for the traditional claims of its efficacy. Although there has been considerable progress in the research on G. procumbens, to date there is no review paper gathering the reported biological activities of G. procumbens. Hence, this review aims to provide an overview of the biological activities of G. procumbens based on reported in vitro and in vivo studies. In brief, G. procumbens has been reported to exhibit antihypertensive, cardioprotective, antihyperglycemic, fertility enhancement, anticancer, antimicrobial, antioxidant, organ protective and antiinflammatory activity. The commercial applications of G. procumbens have also been summarized in this paper based on existing patents. The data compiled illustrate that G. procumbens is a potential natural source of compounds with various pharmacological actions which can be utilised for the development of novel therapeutic agents.